Impact of the updated TNM staging criteria on prediction of persistent disease in a differentiated thyroid carcinoma cohort - Carla Fernanda Nava; André B. Zanella; Rafael Selbach Scheffel; Ana Luiza Maia; Jose Miguel Dora (Archives of Endocrinology and Metabolism)
ABSTRACT Objective: The 8th TNM system edition (TNM-8) released in 2018 presents significant changes when compared to the 7th edition (TNM-7). The aim of this study was to assess the impact of changing the TNM staging criteria on the outcomes in a Brazilian cohort of differentiated thyroid carcinoma (DTC). Subjects and methods: DTC patients, attending a tertiary, University-based hospital, were classified by TNM-7 and TNM-8. Prediction of disease outcomes status of the two systems was compared in a retrospective cohort study design. Results: Four hundred and nineteen DTC patients were evaluated, comprised by 82% (345/419) women, with mean age at diagnosis of 46.4 ± 15.6 years, 89% (372/419) papillary thyroid carcinoma, with a median tumor size of 2.3 cm (P25-P75, 1.3-3.5). One hundred and sixty patients (38%) had lymph node metastases and 47 (11%) distant metastases at diagnosis. Using the TNM-7 criteria, 236 (56%) patients were classified as Stage I, 50 (12%) as Stage II, 75 (18%) as Stage III and 58 (14%) as Stage IV. When evaluated by the TNM-8, 339 (81%) patients were classified as Stage I, 64 (15%) as Stage II, 2 (0.5%) as Stage III and 14(3%) as Stage IV. After a median follow-up of 4.4years (P25-P75 2.6-6.6), the rate of incomplete biochemical and/or structural response was 54% vs. 92% (P = 0.004) and incomplete structural response was 42% vs. 86% (P = 0.009) for patients classified as stage IV by TNM-7 vs TNM-8, respectively. Only 4 (1%) disease-related deaths were recorded. Conclusions: In our cohort, 37% of DTC patients were down staged with the application of TNM-8 (vs. TNM-7). Additionally, TNM-8 seems to better stratify the risk of structural incomplete response at follow-up.